Clients' Perspectives on a Technology-Based Food Assistance Application System. (November 2013) - Heflin, Colleen M.; London, Andrew S.; Mueser, Peter R.
The expansion of e-government is reshaping how disadvantaged groups access the social safety net, yet very little is known about clients' experiences with modernized systems. We examine client experiences applying to the Supplemental Nutritional Assistance Program in one state that has recently moved to an "online-only" system. Overall, more than half of the 26 applicants stated a preference for the traditional caseworker model, even though some of them identified benefits to the modernized, online system. Based on respondents' experiences, we identified four points where the system proved problematic for applicants: (a) Accessing the call centers; (b) completing an eligibility interview; (c) using the paperless system to submit documentation; and (d) obtaining personal assistance to complete the application materials. Findings are relevant for state administrators of social safety net programs, e-government researchers in the public management and public administration fields, and social stratification researchers interested in how institutional processes influence patterns of inequality.